Database Systems for Advanced Applications 17th International Conference, DASFAA 2012, Busan, South Korea, April 15-19, 2012, Proceedings, Part I - Lee, Sang-goo.; Peng, Zhiyong; Zhou, Xiaofang; Moon, Yang-Sae.; Unland, Rainer; Yoo, Jaesoo; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg, 2012)
This two volume set LNCS 7238 and LNCS 7239 constitutes the refereed proceedings of the 17th International Conference on Database Systems for Advanced Applications, DASFAA 2012, held in Busan, South Korea, in April 2012. The 44 revised full papers and 8 short papers presented together with 2 invited keynote papers, 8 industrial papers, 8 demo presentations, 4 tutorials and 1 panel paper were carefully reviewed and selected from a total of 159 submissions. The topics covered are query processing and optimization, data semantics, XML and semi-structured data, data mining and knowledge discovery, privacy and anonymity, data mangement in the Web, graphs and data mining applications, temporal and spatial data, top-k and skyline query processing, information retrieval and recommendation, indexing and search systems, cloud computing and scalability, memory-based query processing, semantic and decision support systems, social data, data mining.
Keywords: Computer science; Database management; Data mining; Information storage and retrieval systems; Multimedia systems; Computer Science; Database Management; Data Mining and Knowledge Discovery; Information Storage and Retrieval; Information Systems Applications (incl. Internet).; Multimedia Information Systems; User Interfaces and Human Computer Interaction